Understanding the interface constitution of a substrate/coating system deposited by cathodic magnetron sputtering HiPIMS - Chabanon, Angelique Annie (Nanyang Technological University, 2022)
Sustainability issues are essential for component performance in many corrosive environments. For this purpose, the development of environmentally friendly, industrially and economically viable surface treatments is performed. In this work, substrate/coating systems developed by HiPIMS process are studied. The objective is to understand and characterize in detail the role of the different interfaces encountered in these systems in order to optimize their resistance to corrosion in nitric acid and seawater. Firstly, the pre-treatment of the substrate by HiPIMS ion etching and its influence on a substrate/metallic bond coat system are studied. Three types of ion etching (Ar+, Ti+ and Zr+) are performed and lead to a modification of the substrate surface by implantation of the sputtered elements on the first nanometers. This leads to the modification of the chemical composition of the passive layer and improves the corrosion resistance of the metal ion-etched substrates in both studied environments. Then, a 200 nm-thick metallic bond coat (Ti/Zr) is deposited on the etched substrates to study the substrate/metallic bond coat interface. The beneficial effect of metal ion etching is still observed after deposition of the bond coat, suggesting that the metal species can act as a preferential nucleation site for metallic layer growth and probably promote a denser film. Secondly, a 5 µm-thick non-optimized substrate/metallic bond coat/oxide coating (TiO2/ZrO2) system is studied. The results indicate that Zr-based systems are promising for corrosion protection in our two study media.